INNOVATIVE AND PROJECT ACTIVITIES OF FUTURE EDUCATION - (:unkn) unknown (My University, 2021)
The article examines the features of the innovative and project activities of future education managers. The authors focus on project technology as one of the forms of innovative methodological technologies for training future education managers, describes the elements of project technology, defines the basic principles of work on a project and the specifics of attracting future education managers to participate in them. The fact is emphasized that future education managers can be active participants in the process of creating a project, develop their own view of information, identify goals, objectives and look for ways to solve them. The purpose of this article is to focus on innovation project activities as one of the forms of innovative methodological learning technologies, to describe the elements of project technology, to highlight the basic principles of work on a project and the peculiarities of attracting future education managers to participate in them.